Contributions to Depressed Affect in Latina Women: Examining the Effectiveness of the Moms’ Empowerment Program - Stein, Sara F. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) is a significant social and public health problem that includes physical violence, sexual violence, threats of physical or sexual violence, stalking, and psychological aggression by an intimate partner. Estimates suggest that 35% of Latinas living in the United States experience IPV in their lifetime, with known severe negative outcomes. One mental health consequence of concern is depression, which disproportionately affects IPV-exposed Latinas. The present study tested the effectiveness of the Moms’ Empowerment Program (MEP), a culturally adapted intervention to reduce depressive symptoms among IPV-exposed Spanish-speaking Latina mothers. Additional psychosocial predictors of levels of depressed affect over time are examined, including levels of post-traumatic stress, IPV exposure, positive parenting, parental acceptance of children’s negative emotions, and maternal employment. Participants (N = 72) were assigned to a treatment or a wait-list comparison condition, and those in the treatment group completed a 10-week group intervention addressing the unique problems associated with IPV exposure, mental health, and parenting among Spanish-speaking Latinas. Results of multilevel modeling revealed that participation in the MEP was associated with significant reductions in depressed affect. Lower levels of post-traumatic stress and higher levels of positive parenting, maternal acceptance of children’s negative emotions, and maternal employment predicted lower levels of depressed affect. The amount of total IPV exposure was not significantly associated with the extent of depressed affect. The MEP represents a culturally tailored, evidence-based intervention to reduce depressed affect among Spanish-speaking Latinas. The clinical implications of the additional predictors of levels of depressed affect are discussed.